Efektivitas Pemberian Aplikasi Siper-B terhadap Pengetahuan, Kepercayaan Diri dan Keterampilan Ibu dalam Merawat Bayi Berat Lahir Rendah - Hanny Krissanti; Ratna Wardani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the effectiveness of providing health education using audio-visual media, namely the application of SIPER-B (Information System for LBW Infant Care) on mothers' knowledge, confidence and skills in caring for low birth weight babies. The research method is quasi-experimental with a pre-test – post-test control group design. The results showed that the knowledge, confidence and skills in the intervention group were higher than in the control group, with a grand mean of knowledge of 19.36, self-confidence of 5.48, skills of 7.88 and a p-value of 0.000. In conclusion, the SIPER-B application effectively increases mothers' knowledge, confidence and skills in caring for babies with low birth weight (LBW). Keywords: LBW, Confidence, Skills, Knowledge